Supercritical CO2 extraction and purification of bioactive compounds in olive leaf with molecularly imprinted polymers - Gomes, Catarina (2022)
Around 4.5 million tons of leaves are generated each year as a by-product of the olive and olive-oil production. These olive leaves must be removed from the fields and olive-mills. Usually they are burned, or else used as fuels or for animal feed. However, olive leaf is extremely rich in bio-resources, being estimated that around 1 million tons of bioactive compounds, 1 million tons of cellulose and 1.5 million tons of lignin are currently underexploited [1]. In particular, the extraction and isolation of high-added value bioactive compounds in olive leaf (e.g. polyphenols, triterpenoids, essential oils, lipids, lignocellulose) is especially appealing due to their high-market potential in the food, feed, chemical, nutraceutical, cosmetic and pharmaceutical sectors